BACK PAIN RISK FACTORS IN ADOLESCENT ATHLETES: SUITABILITY OF A BIOMECHANICAL SCREENING TOOL?. Issue 4 (1st February 2017) - Mueller, Steffen; Mueller, Juliane; Stoll, Josefine; Engel, Tilman; Mayer, Frank
Abstract : Background: Back pain (BP) is already a relevant injury site in adolescent athletes. A valid screening is essential for BP prevention. Objective: To investigate whether a biomechanical screening tool (BST) is suitable to predict BP in adolescent athletes. Design: Longitudinal analysis with 1.9±1.0 yrs between both measurement days. Setting: Medical center of the German Olympic Sports Federation . BST was implemented in the annual (pre-participation) examination of elite athletes. Patients (or Participants): 343 athletes (195 males/148 females, 13±1 yrs, 164±12 cm, 53±13 kg, 5±3 training years, 8±6 training hours per week) out of 20 sport disciplines were included in the study. Interventions (or Assessment of Risk Factors): Subjective BP was assessed using a faces-pain-scale (FPS 1–5: 1=no pain; 2–5=slight- to maximum pain). In addition, postural control (one-legged stance), jumping performance (counter movement/drop jump), and maximum isokinetic trunk extension/flexion strength (60°/sec) was assessed for all athletes. Main Outcome Measurements: Athletes were classified into 4 groups with respect to the course of back pain [(A) no BP (n=206); (B) BP-developers (n=34); (C) persisting BP (n=71); (D) diminishing BP (n=32)]. Outcomes included center of pressure displacement COP [mm], jump height [cm], peak jumping force [N], contact time [ms] and peak torque for trunk extension/flexion [Nm]. Descriptive analysis was followed by two-way ANOVA (repeated measures; α=0.05). Results: Overall, the athletes enhanced trunk strength, jump performance and postural control across the evaluation period. Pain free athletes (A) showed statistically significant higher trunk strength gains (extension/flexion: +45/+37%) compared to athletes developing BP (B: +20/+9%; p<0.05). No differences were observed for jump performance and postural control (p>0.05). Conclusions: Analysing biomechanical variables is valid to identify significantly impaired trunk strength development in athletes with BP incidence. In contrast, jump performance and postural control are of minor relevance. Therefore, poor trunk strength development could serve as back pain risk factor in athletes. Trunk strength training interventions should be recommended.